Design and hardware construction of half bridge series loaded resonant converter / Lina Ayuni Zainal - Zainal, Lina Ayuni (2009)
This paper deals with the analysis, simulation and design of the half bridge series loaded resonant converters which includes both theoretical and practical aspects of this resonant converter design. The simulation was done in PSIM demo 7.1.2. Experimental results on a laboratory are shown to verify the design procedure.